Caregiver Burden, Quality of Life and Related Factors in Family Caregivers of Dementia Patients in Turkey. (2nd August 2020) - Tulek, Zeliha; Baykal, Dilek; Erturk, Sumeyye; Bilgic, Basar; Hanagasi, Hasmet; Gurvit, I. Hakan
Abstract: This study aimed to evaluate caregiver burden and quality of life (QoL) and their predictors in family caregivers of dementia patients. A descriptive cross-sectional survey was carried out with a sample of 102 patients and their family caregivers. The Caregiver Burden Inventory (CBI) and Short Form-12 (SF-12) were used to collect data. CBI mean score was 37.97 ± 21.30. Mean scores of SF-12 sub-domains varied between 36.02 and 77.94 and were significantly lower as compared to normative means of the general population, excluding only the physical health subdomain. Among several patient and caregiver-related correlations, the number of medications and worse cognitive function of the patient, caregiver's age and having limited space at home were found as predictors of burden, whereas caregiver's chronic disease and having a limited space were predictors of QoL. Also, the burden and QoL were correlated. This study demonstrated a high burden and low QoL in dementia caregivers. In societies where caregivers are mostly informal such as that in Turkey, supportive systems should be established.